2019
DOI: 10.3390/w11091780
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Intermittence and Pressure Differentials in Hydrogen Sulfide Concentration in a Gravity Sewer

Abstract: The work presented herein was carried out to assess the effect of intermittent pumping events in sewer headspace pressure differentials, as well as their relationship with hydrogen sulfide gas concentration. A full scale gravity sewer in Portugal, located downstream of several pumping stations, was used as the guiding case study. Under normal system operation, pressure difference between the outside atmosphere and the sewer headspace seemed to influence the in and out-gassing of gas pollutants emitted through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Nonetheless, most field studies and model applications found in the literature refer to either domestic wastewater conveyance networks [10][11][12][13], or lab/pilot scale abatement strategies for source control, for varied industrial sectors [42,43]. Industrial effluents with significant pollutant loads, in terms of sulfide and other relevant parameters for the sulfur cycle, may require higher reagent dosage to control the fate of sulfide and H 2 S along the sewer system.…”
Section: H 2 S Modelling Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, most field studies and model applications found in the literature refer to either domestic wastewater conveyance networks [10][11][12][13], or lab/pilot scale abatement strategies for source control, for varied industrial sectors [42,43]. Industrial effluents with significant pollutant loads, in terms of sulfide and other relevant parameters for the sulfur cycle, may require higher reagent dosage to control the fate of sulfide and H 2 S along the sewer system.…”
Section: H 2 S Modelling Approachesmentioning
confidence: 99%
“…This indicates that wastewater discharges may have occurred where sulfide was not present, and H 2 S in the system can be expected to correlate heavily with the timing of tanning industry discharges. In addition, it is known that headspace pollutant concentrations are also heavily influenced by ventilation parameters, such as wastewater drag, turbulence, wind speed, fluctuations in wastewater levels, buoyancy, temperature and headspace pressurisation [13], which illustrate the complexity in addressing and accurately modelling these processes.…”
Section: Model Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Some of the previously mentioned studies [20,21,24] allow us to estimate the amount of H2S formed inside single sewer sites and on sites consisting of a complex of networks and structures. However, up to date, there are no methods to determine the amount of gases that are released in specific sewerage facilities.…”
Section: Such Factors Include: Climatic Characteristicsmentioning
confidence: 99%
“…Work is also under way to study the factors affecting the gases emission within networks and their distribution. [20][21][22], the type of transportation networks (combined, separate) and hydraulic characteristics of the flow in them (slope, filling, length) [23,24], the velocity of air masses movement in the headspace of structures and sewers [25], changes in pressure within the network [22], changes in properties and composition of wastewater [26][27][28].…”
Section: Introductionmentioning
confidence: 99%